Ultrasound assisted extraction of pectin from Trachystemon orientalis L. - KESKIN, Saban; KESKIN, Merve; KOLAYLI, Sevgi (Journal of Medicinal Herbs and Ethnomedicine, 2019)
Pectin, a natural bio polymer, has wide range of applications in different fields because of its gelling, stabilizing and emulsifying ability as food additive/preservative and drug carrier etc. Main objective of this study was to describe the extraction of pectin for the first time from Trachystemon orientalis L., a medicinal plant grown in black sea region of Turkey. Pectin was extracted from the plant by ultrasound assisted acid hydrolysis method. Obtained pectin was characterized by using ATR-FT-IR and TGA methods. It was observed that the plant contained 2.5% pectin (0.25 g pectin/ per 10 g dried sample). Obtained pectin was labeled as High Methyl esterified Pectin (HMP) as its methoxyl- content was found to be 80% by using titrimetric method. ATR-FT-IR and TGA images were obtained as well. It can be concluded that Trachystemon orientalis L. could be a new source for pectin production for food and pharmaceutical industries.